The kinetics of IgG Antibodies in Critically Ill Patients - Jabrane, mona; Asmaa Lamrani Hanchi; Nabila Soraa; Rabab Bellaka; Abdelhamid Hachimi, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
the kinetics of SARS-CoV-2 antibodies response and factors predicting igG levels are still limited. We report a prospective analytical study of patients admitted for SARS-cov-2 in the medical intensive care unit of the Mohammed VIth University Hospital of Marrakech for three months.We measured the level of igG antibodies to SARS-Cov-2 on plasma blood samples from all patients collected on admission and then every seven days respectively until discharge or death. The kinetics of antibodies with disease progress were analyzed. The mean igG levels increased between ICU admission till day 21, then they dropped on day 28. Critical patients had higher igG levels than severe ones with no statistically significant difference. Between day one and day 14, males had higher igG levels than females; however, females had higher levels on days 21 and 28 with a statistically significant difference on day 28. On the chest CT scan, patients with ground-glass opacities and/or crazy paving distribution of 75% or more had higher igg levels with a statistically significant difference on day 7. In terms of mortality, deceased patients had higher igG levels with no statistically significant difference than survivors. Our results may suggest the incrimination of SARS-cov-2 igg antibody high level as a prognostic factor for disease severity.